Systematic Review Of Physical, Psychosocial And Spiritual Impact Of Post Acute Stroke Patients With Home Dwelling Care Approach - Muqarrobin, Aoladul; Chayati, Nur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Stroke is a severe problem that is physically, psychologically, and spiritually complex. There should be a consideration of increasing self-ability in stroke patients through continued care at home to help patients to improve their quality of life. This study aims to analyze the impact of home-based care on the physical, psychological, and spiritual conditions of post acute stroke patientsMethods: This research is a systematic review. The research source came from two databases, namely ProQuest and EBSCO, with the keywords